2011
DOI: 10.1002/jrs.3005
|View full text |Cite
|
Sign up to set email alerts
|

Morphine studied by vibrational spectroscopy and DFT calculations

Abstract: Morphine is a highly potent opiate analgesic drug considered to be the prototypical opioid. It is metabolized in the body to morphine-3-O-glucuronide, which is antagonistic to the analgesic effects of the drug. Other forms of morphine of biological activity are salts used in medical dosing. In order to investigate morphine, its metabolite and salts and as well as pharmaceutical product, Fourier transform (FT) infrared and Raman spectroscopy were used. Experimental spectra of morphine were interpreted with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
(17 reference statements)
1
18
0
Order By: Relevance
“…Cinchona alkaloids have already been studied by some chromatographic and fluorescence methods; however, only a few seem to be of great importance: TLC and HPLC with fluorescence detection or densitometric evaluation, stereoselective non aqueous capillary electrophoresis, fluorescence life‐time determination, and circular dichroism . On the other hand, some studies have already shown usefulness of vibrational spectroscopy for identification and determination of isolated alkaloids and for the localization of these alkaloids in plants and related products, including the application of Vibrational Optical Activity (VOA) methods . Furthermore, because compounds like QN and QND show different properties in their pharmaceutical usage, it seems to be vitally important to differentiate between the individual pseudoenantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…Cinchona alkaloids have already been studied by some chromatographic and fluorescence methods; however, only a few seem to be of great importance: TLC and HPLC with fluorescence detection or densitometric evaluation, stereoselective non aqueous capillary electrophoresis, fluorescence life‐time determination, and circular dichroism . On the other hand, some studies have already shown usefulness of vibrational spectroscopy for identification and determination of isolated alkaloids and for the localization of these alkaloids in plants and related products, including the application of Vibrational Optical Activity (VOA) methods . Furthermore, because compounds like QN and QND show different properties in their pharmaceutical usage, it seems to be vitally important to differentiate between the individual pseudoenantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…For this experiment, we particularly tracked the spectral region associated with OH functional group being our unique vibrational band marker associated with the template (morphine). The typical vibrational bands of morphine were given the following assignments based on literature: strong signal at 1050–1200 cm −1 is due to COC stretching vibrations; 1600–1700 cm −1 is due to the skeletal vibration of CC; 2800–3000 cm −1 is due to CH stretching and deformation vibration; and 3200–3600 cm −1 a strong vibration is due to OH stretch . The peak at 1600–1700 cm −1 is due to the CC vibration of morphine that overlaps with CO present in our cross‐linker (MBA).…”
Section: Resultsmentioning
confidence: 93%
“…The typical vibrational bands of morphine were given the following assignments based on literature: strong signal at 1050-1200 cm −1 is due to C O C stretching vibrations; 1600-1700 cm −1 is due to the skeletal vibration of C C ; 2800-3000 cm −1 is due to C H stretching and deformation vibration; and 3200-3600 cm −1 a strong vibration is due to OH stretch. [ 58,59 ] The peak at 1600-1700 cm −1 is due to the C C vibration of morphine that overlaps with C O present in our cross-linker (MBA). Likewise, the peaks at 1050-1200 cm −1 are due to C O C stretching vibrations of morphine that overlaps with the C H out-of-plane deformation from poly( p -AS).…”
Section: Functional Group Characterization and Template Removal Studimentioning
confidence: 98%
“…Nondestructive analysis of toxic substances has been carried out using vibrational spectroscopy—Raman and Fourier transform infrared spectroscopy (FTIR). Both are fast techniques that can obtain spectra without using reagents for small samples, permit to the use of portable devices and optical fibers for remote analysis, and identify substances quickly . Vibrational spectroscopy techniques are based on the fact that chemical bonds of substances have specific vibration frequencies that correspond to the vibrational energy levels of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Both are fast techniques that can obtain spectra without using reagents for small samples, permit to the use of portable devices and optical fibers for remote analysis, and identify substances quickly. [11,12] Vibrational spectroscopy techniques are based on the fact that chemical bonds of substances have specific vibration frequencies that correspond to the vibrational energy levels of the molecule. Although Raman spectroscopy is based on the inelastic scattering of photons by molecules as a function of excitation by ultraviolet, visible, or infrared radiation, FTIR spectroscopy is based on the absorption of infrared radiation by the molecule.…”
mentioning
confidence: 99%